Grazing dampens the positive effects of shrub encroachment on ecosystem functions in a semi‐arid woodland. Issue 4 (4th June 2013) - Eldridge, David J.; Soliveres, Santiago; Bowker, Matthew A.; Val, James
Summary: The encroachment of woody plants into grasslands, open woodlands and savannah has been widely reported over the past few decades. Overgrazing is a probable cause of shrub encroachment and could be a stronger driver of declining ecosystem structure and functioning in shrublands than encroachment per se . We examined the relative effects of changes in shrub cover and grazing rate on ecosystem functions at sandy and loamy sites in eastern Australia varying in shrub cover and grazing. Our aim was to test the notion that the negative effects on ecosystem functioning commonly attributed to encroachment are more likely due to grazing than to increase in shrub cover per se . Structural equation modelling indicated a generally strong positive effect of increasing shrub cover, and a generally negative, or slight effect of grazing on multiple measures of ecosystem function related to plant productivity, water infiltration, nutrient cycling and surface stability. On loamy soils, grazing generally dampened the positive effects of increasing shrub cover on most response variables. On sandy soils, however, although there were generally stronger effects of grazing, most attributes did not change in response to increasing shrub cover. Synthesis and applications . Our results indicate that, contrary to the prevailing opinion, increasing shrub cover was generally associated with increases (or no change) in functional and structural measures indicative of healthy systems. The dampening of the positive effects of shrub cover caused by grazing was site (soil texture) specific, reinforcing the notion that the effects of increasing shrub cover and their interaction with grazing are context dependent. Our study provides the basis for improved understanding and management of shrublands for a number of competing goals and suggests that managing grazing rates is a better strategy than focusing on shrub removal. Using low levels of grazing is likely to maximize the benefits from shrublands, such as the maintenance of biodiversity, water infiltration and C sequestration, while maintaining a productive herbaceous community. Abstract : Our results indicate that, contrary to the prevailing opinion, increasing shrub cover was generally associated with increases (or no change) in functional and structural measures indicative of healthy systems. The dampening of the positive effects of shrub cover caused by grazing was site (soil texture) specific, reinforcing the notion that the effects of increasing shrub cover and their interaction with grazing are context dependent. Our study provides the basis for improved understanding and management of shrublands for a number of competing goals and suggests that managing grazing rates is a better strategy than focusing on shrub removal. Using low levels of grazing is likely to maximize the benefits from shrublands, such as the maintenance of biodiversity, water infiltration and C sequestration, while maintaining a productive herbaceous community.